The impact of family social support on academic resilience in Indonesian and Turkish students: the mediating role of self-regulated learning - Fitriah M. Suud; Zuhal Agilkaya-Sahin; Tri Na’Imah; Muhammad Azhar; Mariah Kibtiyah (International Journal of Adolescence and Youth)
This study examines the influence of family social support on student resilience and self-regulated learning (SRL), as well as the role of SRL as a mediator for Indonesian and Turkish students. This quantitative method used three research scales to answer the research questions: resilience, family social support, and self-regulated learning. The study included 606 Indonesian respondents and 504 Turkish respondents. In this study, the researchers used a structural equation model based on partial least squares to perform data analysis. The results showed that Indonesian students had a higher average academic resilience score than Turkish students. Turkish students’ family social support scores were higher than Indonesian students. The bootstrapping method demonstrated a positive indirect effect of SRL on the relationship between family social support and academic resilience. Hence, SRL is a good variable that connects family social support with academic resilience.